2010
DOI: 10.1088/1741-2560/7/2/026006
|View full text |Cite
|
Sign up to set email alerts
|

Selective stimulation of the human femoral nerve with a flat interface nerve electrode

Abstract: In humans, we tested the hypothesis that a flat interface nerve electrode (FINE) placed around the femoral nerve trunk can selectively stimulate each muscle the nerve innervates. In a series of intraoperative trials during routine vascular surgeries, an eight-contact FINE was placed around the femoral nerve between the inguinal ligament and the first nerve branching point. The capability of the FINE to selectively recruit muscles innervated by the femoral nerve was assessed with electromyograms (EMGs) of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(111 citation statements)
references
References 40 publications
3
106
0
Order By: Relevance
“…Designing models of nerve-cuff electrodes to selectively stimulate distal musculature using fascicular anatomy [16] has been accomplished using similar data for the femoral nerve [22]. These studies have led to intraoperative verification of the designs and approval for human feasibility trials [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Designing models of nerve-cuff electrodes to selectively stimulate distal musculature using fascicular anatomy [16] has been accomplished using similar data for the femoral nerve [22]. These studies have led to intraoperative verification of the designs and approval for human feasibility trials [24].…”
Section: Discussionmentioning
confidence: 99%
“…Modeling and simulation studies based on the detailed femoral fascicular anatomy [22] have been successfully employed to design and optimize implantable femoral nerve-cuff electrodes [16]. This model-driven approach to designing selective electrodes for the femoral nerve has been verified intraoperatively [23], and the resulting devices have been approved for human feasibility trials [24]. The first step in repeating this design and optimization procedure for the sciatic nerve is the specification of the fascicular structure of the branches that innervate ankle musculature.…”
Section: Neural Prostheses For Ankle Controlmentioning
confidence: 99%
“…3) [63,66,105,151,161]. Additionally, intraoperative studies in the human femoral nerve showed that muscles innervated by the femoral nerve could be independently and selectively stimulated with a FINE device [133]. Surgical placement of FINE around the femoral trunk leads to selective activation of leg muscles, thereby aiding patients who suffer from lower trunk paralysis to stand from a sitting position [134].…”
Section: Flat Interface Nerve Electrodesmentioning
confidence: 99%
“…Selective stimulation of efferent neurons (similar to the afferent Type Ia and Ib neurons we are targeting) in the human PNS has been demonstrated in [21], [22] to occur with charge packets of between 11±5 nC to 29±17 nC. Given these values our stimulator will be designed to deliver up to 50 nC in a 100 μs pulse (a common pulse duration).…”
Section: A Energy Efficiencymentioning
confidence: 99%